Information Literacy (ALFIN), using a Virtual Teaching and Learning Platform in Higher Education (Educational Knowledge, 2016)
This article reports on the development of the project, “Plan for Improving Learning Resources Using New Technologies on the Three Campuses of the University of Los Lagos,” within the framework of the MECESUP ULA 1109 project, entitled “Program for Improving the Quality and Equity of Higher Education.” The actions of this project focused on the development of information literacy skills, which—once the project's implementation and evaluation were completed—were incorporated into the study modules of the ICT-related transversal courses offered by the institution. These skills have been broken down into three levels of development to facilitate learning. For each level, the content involved in developing the aforementioned skills is linked to its corresponding learning outcomes.During one academic semester, the skills, achievement levels, content, and learning outcomes were incorporated into the ICT-related transversal courses using the institution's Teaching and Learning Platform (PLATEA) as a pilot program. Furthermore, the social commitment of university libraries to education through information literacy (ALFIN) is highlighted, contributing to the development of these skills. In this regard, librarians, in addition to their traditional work in technical processes, reference, and circulation, support educational efforts, working alongside faculty to contribute to students' learning processes.It is explicitly stated that promoting the development of information literacy skills in university students requires collaborative work between librarians and faculty. The implementation process of ALFIN, its content, and some results are also described.
Keywords: Information Literacy; ALFIN; University Libraries; Education in Information; Education Platforms; Transversal Competencie